2007
DOI: 10.1016/j.mambio.2006.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Diet of the brown hare (Lepus europaeus) and food availability in northern Patagonia (Mendoza, Argentina)

Abstract: The brown hare, a Leporid widespread in the world, is now dispersed across Argentina after its introduction at the end of the 19th century. Studies on hare feeding ecology are important to evaluate a potential competition with domestic and native wild herbivores. This study analyses the brown hare diet in relation to food availability, and dietary overlaps with several herbivores in northern Patagonia. Food availability was estimated by point-quadrat transects, and hare diet by microhistological analysis of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 16 publications
4
27
0
3
Order By: Relevance
“…The ability of the European hare to become a highly effective alien invasive species has been demonstrated both in Sweden, where it has displaced the native mountain hare (Thulin 2003;, and in northern Patagonia where mara (Dolichotis patagonum) populations have been depressed or displaced since its introduction in the late 1800 s (Puig et al 2006). The present study indicates that the European hare poses a significant threat to the ecological security of the Irish hare.…”
Section: Discussionmentioning
confidence: 61%
“…The ability of the European hare to become a highly effective alien invasive species has been demonstrated both in Sweden, where it has displaced the native mountain hare (Thulin 2003;, and in northern Patagonia where mara (Dolichotis patagonum) populations have been depressed or displaced since its introduction in the late 1800 s (Puig et al 2006). The present study indicates that the European hare poses a significant threat to the ecological security of the Irish hare.…”
Section: Discussionmentioning
confidence: 61%
“…Studies on the brown hare, L. europaeus (e.g., Frylestam 1986;Chapuis 1990;Homolka and Heroldova 2003;Reichlin et al 2006;Puig et al 2007), on the mountain hare, L. timidus (e.g., Johannessen and Samset 1994; Wolfe et al 1996;Dingerkus and Montgomery 2001), and on the black-tailed 1982; Johnson and Anderson 1984) showed that grasses are generally the main component of their diet. However, available data also suggests the occurrence of temporal and spatial variation in the diets depending on food availability.…”
Section: Introductionmentioning
confidence: 99%
“…Hare droppings were located by searching a predetermined transect inside the Miscanthus crops and were easily distinguishable from other sympatric species such as rabbits (Oryctolagus cuniculus), based on their size, shape and appearance, with large observable plant fragments on the surface. At least 10 droppings from separate clumps located several meters away from each other were collected from each Miscanthus field to ensure a representative assessment of diet (Puig et al 2007). Six combined samples obtained from hare droppings were analysed from each Miscanthus block in each of three seasons (winter, spring, summer), totalling 36 samples.…”
Section: Data Collectionmentioning
confidence: 99%